Ionic liquid pretreatment of biomass for sugars production: Driving factors with a plausible mechanism for higher enzymatic digestibility. (20th September 2016) - Raj, Tirath; Gaur, Ruchi; Dixit, Pooja; Gupta, Ravi P.; Kagdiyal, V.; Kumar, Ravindra; Tuli, Deepak K.
Graphical abstract: Investigation of the ionic liquids pretreatment of lignocellulosic biomass for producing fermentable sugar and analyzing the impact of various parameters over the enzymatic digestibility with a plausible mechanism. Highlights: Treatment efficiencies of five ionic liquids studied over mustard stalk and wheat straw. [C2 mim][OAc] with 1.32 β-value resulted 97.7% of glucose using 10 FPU/g of biomass. Viscosity and surface tension of ILs have a negative correlation with glucose yields. Explanation of the transformation from cellulose I to II using PXRD and FT-IR. Postulation of the mechanism for improved enzymatic hydrolysis on cellulose-II. Abstract: In this study, five ionic liquids (ILs) have been explored for biomass pretreatment for the production of fermentable sugar. We also investigated the driving factors responsible for improved enzymatic digestibility of various ILs treated biomass along with postulating the plausible mechanism thereof. Post pretreatment, mainly two factors impacted the enzymatic digestibility (i) structural deformation (cellulose I to II) along with xylan/lignin removal and (ii) properties of ILs; wherein, K-T parameters, viscosity and surface tension had a direct influence on pretreatment. A systematic investigation of these parameters and their impact on enzymatic digestibility is drawn. [C2 mim][OAc] with β-value 1.32 resulted 97.7% of glucose yield using 10 FPU/g of biomass. A closer insight into the cellulose structural transformation has prompted a plausible mechanism explaining the better digestibility. The impact of these parameters on the digestibility can pave the way to customize the process to make biomass vulnerable to enzymatic attack.